1988
DOI: 10.3354/meps050073
|View full text |Cite
|
Sign up to set email alerts
|

Feeding reduction, reproductive failure, and mortality in Mytilus edulis during the 1985 'brown tide' in Narragansett Bay, Rhode Island

Abstract: ABSTRACT. During summer 1985, reduced feeding, reproductive failure and massive mortalities were observed in populations of the blue mussel Mytilus edulis during an extremely dense algal bloom (106 cells ml-l) in Narragansett Bay, Rhode Island (USA). The dominant alga was an extremely small (1 to 211m diameter) non-flagellated chrysophycean form previously unobserved in coastal or offshore waters. Effects of the alga on clearance rates of mussels were tested using natural particulates (NBP) collected from Narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 37 publications
(46 reference statements)
3
46
0
1
Order By: Relevance
“…Reductions in A. tonsa body size, gut pigment content, and egg production during the brown tide suggest that this alga was poorly grazed. The cause of the unpalatability of brown tide algae is not clear, but Tracey et al (1988) suggested that an external layer of polysaccharidelike material covering the cell may interfere with motion of mussel gill cilia, either by clogging or chemical irritants or toxicants.…”
Section: Pjesteria Toxin Neurotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in A. tonsa body size, gut pigment content, and egg production during the brown tide suggest that this alga was poorly grazed. The cause of the unpalatability of brown tide algae is not clear, but Tracey et al (1988) suggested that an external layer of polysaccharidelike material covering the cell may interfere with motion of mussel gill cilia, either by clogging or chemical irritants or toxicants.…”
Section: Pjesteria Toxin Neurotoxicitymentioning
confidence: 99%
“…Although picoplankters the size of A. anophag&erens can be eaten by filter-feeding bivalves (Tracey 1988), most grazing on these small cells would be presumed from heterotrophic protists. Mesozooplanktonic suspension-feeders such as copepods are thought to be unable to efficiently graze on picoplankters, but copepods are known to prey on the heterotrophic protists that eat picoplankters (Turner and Roff 1993).…”
Section: Interactions Of Toxic Phytoplankters With Microzooplanktonicmentioning
confidence: 99%
“…The ability of a HAB species to build up population size under specifi c conditions is therefore related to the availability of suffi cient nutrients to sustain it and to reduction in grazing and mortality rates. States, where suppression of grazing occurs above a threshold concentration (Tracey, 1988) (Fistarol et al, 2004). Cyanobacteria, in particular, establish mutually benefi cial consortia by chemotactically attracting and supporting microorganisms involved in nutrient cycling and the production of growth factors (Paerl and Millie, 1996).…”
Section: Population Dynamics Of Habsmentioning
confidence: 99%
“…Brown tides have caused significant environmental damage and economic loss, especially in Long Island waters (Bricelj & Lonsdale 1997). Although not acutely toxic, populations of economically valuable bivalve molluscs (most notably scallops) were severely affected by high abundances of A. anophagefferens, because the feeding activities of these species and other bivalves ceased during blooms of the alga (Bricelj & Malouf 1984, Tracey 1988, Bricelj & Kuenstner 1989. A narcotic effect of the alga has been described (Gainey & Shumway 1991) and 'threshold' abundances that cause cessation of feeding have been documented (Bricelj et al 2001).…”
Section: Introductionmentioning
confidence: 99%